Earnings management and auditor specialization in the post-sox era: An examination of the banking industry - DeBoskey, David Gregory; Jiang, Wei (Journal of Banking & Finance, 2012)
This study examines the impact of auditor specialization on bank loan loss provisions for a large cross-section of US banks for the period 2002–2006. We find a positive relationship between earning (before provision) and loan loss provision, suggesting that bank managers use LLP to smooth earnings in the post-SOX period. However, this relationship is significantly moderated by audit industry expertise, providing strong evidence that industry specialization constrains income smoothing. In further analysis, we find some evidence that auditor specialization is more effective in reducing potentially incoming-increasing earnings management. Our results hold after controlling for self-selection bias and are robust to alternative measures of industry specialization. Overall, our findings support the conclusion that audit industry expertise plays an effective monitoring role in constraining management’s discretionary accounting choices.